Design 3D printing cementitious materials via Fuller Thompson theory and Marson-Percy model. (28th February 2018) - Weng, Yiwei; Li, Mingyang; Tan, Ming Jen; Qian, Shunzhi
Highlights: Influence of gradations on rheology of cementitious materials has been investigated. Effect of rheology of 3DP materials on printability and buildability are studied. Appropriate 3DP materials can be designed by applying Fuller Thompson Theory. Abstract: Cementitious materials for 3D printing have special requirements for rheological properties, which are significantly affected by many factors, including sand gradation and packing fraction. Fuller Thompson theory and Marson-Percy model are classic approaches for sand gradation and packing fraction optimization, respectively. This paper attempts to apply Fuller Thompson theory and Marson-Percy model in designing cementitious materials for 3D Cementitious Materials Printing (3DCMP). Various gradation methods adopted in this study were Fuller Thompson gradation (mixture A), uniform-gradations (mixture B and C), gap-gradations (mixture D and E). Besides these mixtures with special gradation approaches, one mixture using natural river sand (mixture F) was prepared as well. Rheological properties were characterized by static/dynamic yield stress and plastic viscosity in Bingham Plastic model. Buildability was examined by printing a column with 10 cm inner diameter via a gantry printer. Rheological test results indicate that mixture A designed by continuous gradation possesses the highest static/dynamic yield stress and lowest plastic viscosity. During printing test for buildability, mixture A can easily reach up to 40 layers without notable deformation, while all other mixtures deformed noticeably and fell down before the 35th layer. Finally, a large-scale printing was carried out with mixture A and a structure with the height of 80 cm was printed successfully without notable deformation. Density, compressive strength and flexural strength of printed filaments were also characterized. Mechanical performance test results illustrate mixture A has the highest density and appropriate compressive strength, and a relative high flexural strength at different curing ages. These results indicate that Fuller Thompson theory and Marson-Percy model can serve as a reasonable guide for material rheology design for 3DCMP.